Salivary sialic acid, protein, salivary flow rate, pH, buffering capacity and caries indices in subjects with Down's syndrome - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (My University, 1999)
OBJECTIVES: The aim of this study was to compare salivary sialic acid, protein, salivary flow rate, pH and buffering capacity and caries indices between subjects with Down's Syndrome and healthy controls. METHODS: Unstimulated mixed saliva was collected from 26 Down's syndrome subjects and 25 healthy subjects of age range 6-24 years. Total protein was determined by the method of Lowry and total sialic acid using Ehrlich reagent. Laemmli SDS-polyacrylamide gel electrophoresis was also carried out. RESULTS: Buffering capacity and pH were quite similar for both groups. For permanent dentition subjects pH was significantly higher (P = 0.03) in the Down's syndrome group. The salivary flow rate of the Down's syndrome subjects was significantly lower (P < 0.01) than that of healthy controls and the Down's syndrome subjects' salivary protein and sialic acid levels were significantly higher (P < 0.001). The ratios of total sialic acid to total protein were significantly higher (P < 0.001) in the Down's syndrome group. However, salivary sialic acid expectoration rates, a means of compensating for flow rate differences, were significantly lower (P = 0.01) in the Down's syndrome subjects than in controls. Electrophoresis revealed no significant differences between the protein bands of the groups. There were no significant differences in caries indices between groups, even when compensated for age, nor in the salivary parameters within groups between sexes. CONCLUSIONS: Total salivary sialic acid in Down's syndrome subjects, higher in terms of levels but lower in terms of expectoration rates, was significantly different from that of controls of similar caries indices.
Keywords: Adult; Female; Humans; Adolescent; Male; Child; Down Syndrome; Hydrogen-Ion Concentration; Saliva; Age Factors; DMF Index; N-Acetylneuraminic Acid; Electrophoresis, Polyacrylamide Gel; Sex Factors; Buffers; Salivary Proteins and Peptides; Secretory Rate; Sodium Dodecyl Sulfate; Surface-Active Agents